Hubungan Perbedaan Beban Trauma Dengan Gambaran Histopatologi Hematoma Otak Tikus Pasca Cedera Otak Traumatik: The Relationship between Trauma Load Differences and Histopathological Description of Rat Brain Hematoma Post Traumatic Brain Injury - Gibran Ihza Sukma; Rohadi Rohadi; Lale Maulin Prihatina; Zikrul Haikal (LPPM Universitas Mataram, 2023)
Traumatic brain injury is defined as trauma to the head that can cause physical, intellectual, emotional, social or behavioral changes. Traumatic brain injury is one of the leading causes of morbidity and mortality worldwide. Brain injury Traumatic disorders are among the most common disorders in neurology. in the brain, it accounts for 2 to 15% of all head injuries. This study aims to determine the histopathological picture of brain hemorrhage in rats after experiencing traumatic brain injury and to analyze the relationship between differences in trauma load and the histopathological appearance of brain hemorrhage in rats after experiencing traumatic brain injury. This research is an experimental study conducted by giving treatment to the object under study and then observing it. Sampling in this research will use purposive sampling. Where the researcher has determined the criteria of the sample to be used in the study so that it can represent the population. : The results of this study there was no significant relationship between the percentage of the degree of brain hematoma in rats after experiencing traumatic brain injury. These results explain that bleeding in the brain usually progresses about 4-8 hours after brain injury occurs. In addition, the percentage of bleeding areas with trauma burden was p = 2.890.